“Film-Symphonie vom Leben und Sterben der Blumen”: Plant Rhythm and Time-Lapse Vision in Das Blumenwunder - Blankenship, Janelle (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2010)
This essay analyzes the use of time-lapse cinematography in the early 20th century to unlock worlds hitherto “closed to man” (Balázs). I demonstrate how the new “image worlds” of time-lapse influenced biologists such as Jakob von Uexküll and 1920s avant-garde theorists alike. Using the 1926 hybrid German “cultural film” Das Blumenwunder (The Miracle of Flowers) as my primary case study, I examine how the film aims to present the “inner rhythm” of plants as an alternative temporality, which challenges an anthropocentric world view and at the same time dialogues with the ecstatic rhythms of modern dance. I discuss the film’s self-reflexive use of time-lapse technology, its reception history in the context of the avant-garde and new trends in reform pedagogy, and the specific use of Ausdruckstanz choreography to respond to industrial rhythms and to create a new mimetic form of affect.